Computerized tomography scan of the brain in a community study of neurological impairment in Kenya. - Njuguna, P; Mungala-Odera, V; Chong, W; Meehan, R; Newton, C (2007)
Neurological impairment is common in resource-poor countries, but its causes are not clear. Computerized tomography (CT) of the brain has been used to determine the cause of brain insults that may manifest as neurological impairments. The authors conducted a community survey in Kilifi of 10 218 children aged 6 to 9 years to detect neurological impairment. From this survey, 34 children were identified, of whom 16 had motor deficits, 11 complex partial seizures, 4 microcephaly or macrocephaly, and 3 severe developmental delay. These children were assessed with elicitation of history, physical examination, and CT scan of the brain. Sixteen (47%) of the scans showed abnormalities: cerebral atrophy (n = 9), schizencephaly (n = 3), periventricular leukomalacia (n = 2), porencephalic cyst (n = 1), and agenesis of the corpus callosum (n = 1). The minimum prevalence of abnormalities on the CT scan of the brain is 1.56 of 1000, and the prevalence of schizencephaly is 0.29 of 1000. Motor impairments were more likely to show abnormality than the other indications. CT abnormalities are common in children with neurological impairment in Kenya, but the appearances did not identify a major cause.